Digital Transformation in Modern Business Management: Strategies for Sustainable Competitive Advantage (مجلة العلوم الشاملة, 2025)
Digital transformation has become a key focus area for companies nowadays. Organisations that resist the transformation may lose to their competitors. In this article, we are going to find out how digital transformation strategies could lead to an advantage in today’s business management. This study aims to combine current understanding of how businesses use digital technology to secure a sustainable advantage over competitors. By analysing the theories, strategies, implementation, and cases, we will conduct a study.  The article examines a number of basic issues, which include changes happening in the organisation, key digital technologies (artificial intelligence, cloud computing, and Internet of Things), imperatives around change management, algorithms and data-driven decision making, workforce re-skilling, and technology frontiers. Furthermore, it highlights essential impediments to change. This includes resistance from below, technical obstacles, financial constraints, cybersecurity hurdles, and further challenges. It also provides recommendations for sustainable success. This enables a process of clarification for academic rigour and actionable insight for scholars, practitioners and organisational leaders alike in their quest for digital transformation.